Post-Operative Outcomes of Intravenous Lidocaine Infusion on Major Abdominal Surgery in Pediatric Patients: A Randomized Control Trial in a Tertiary Care Hospital - Saha, Nirupama; Khan, Nadiuzzaman; Zahid, Mirza Kamrul; Talukder, Shah Alam; Meftahuzzaman, ASM (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Post-operative outcomes of a major abdominal surgery depend on careful & effective post-operative management. But it is a critical job especially in children. Obtaining adequate analgesia after major surgery is a problematic issue and postoperative pain still imposes a major burden of suffering in surgical patients. Objectives: The principle objectives of the study is to evaluate the effects of intravenous lidocaine infusion in pain management of pediatric population undergone in major abdominal surgery; to reduce post-operative morbidity & enhance better surgical outcome in children. Methodology: This is a randomized control trial carried out from January 2015-June2015,in a tertiary care hospital among 60 cases of 4 to 14 years children with major abdominal surgery without having any pulmonary, cardiac, hepatic or renal insufficiency. Grouping of patients that is lidocaine infusion group (Group A) and control group (Group B) was made among admitted cases for elective abdominal surgery by simple random technique by means of lottery. For assessment of postoperative pain FLACC Scale was used in both groups. Clinical examination findings & specifically designed data collection sheet with a set questionnaire were used as research instruments. Formulated data was analyzed by SPSS version 17, taking p value <0.05 as significant. Results: It is noted that, after 24 hours of operation most of the patients 56.7% of group A had mild pain whereas 90% patients of group B had moderate pain (p<0.001)& during that time there was no patient with severe pain in group A whereas in group B 10% patients were with severe pain. At 48 hours, pain was absent in 13.3% children of group A and 6.7% in group B. In group A most of the children 76.7%had mild pain compared to moderate pain 18 (60%) in group B children at that hours (P<0.001). Again, regarding required amount of analgesics, patients received I/V lidocaine required less amount of analgesics than its counterpart. In present study, complications was noted only 3.3% patien in group A, where as in the opposite group it was found in 23.3% & p was <0.05. In group A, in 50% patients post operative bowel sound was returned within 72 hours, compared to 73.3% patients in group B. The p value was 0.001. About post-operative hospital stay, 83.3% children of the group A were released from hospital after 5th P.O.D whereas, in group B, only 50% children were released after 7th P.O.D of operation. The P value was 0.03 that is also significant. Conclusion: Intravenous lidocaine could improve immediate and late post-operative pain with early recovery after major abdominal surgery in children & it can contribute to rapid postoperative rehabilitation programs. J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 23-27